Experimental Study on the Seismic Performance of Buckling-Restrained Braces with Different Lengths - Kechuan Wu; Guanglan Wei; Chi Lin; Longfei Zhang; Wenzheng Yu; Xiang Lan (Buildings)
To investigate the differences in seismic performance of buckling-restrained braces (BRBs) with significantly different lengths and to explore the influence of length on the energy dissipation efficiency of BRBs within the same structure, this study designed and fabricated two BRBs with lengths of 8.5 m and 3 m based on an actual engineering project. Low-cycle reciprocating load tests were conducted to compare the performance of the two BRBs in terms of hysteretic energy dissipation capacity, tension–compression bearing capacity imbalance coefficient, cumulative plastic deformation capacity, and low-cycle fatigue life. Additionally, the energy dissipation and damping efficiency of BRBs of different lengths within the same structure was analyzed. The results indicate that under cyclic loading based on design displacement, the 8.5 m BRB exhibits a greater equivalent viscous damping ratio, cumulative hysteretic energy dissipation, and cumulative plastic deformation, leading to more efficient energy dissipation and damping effects. The length of the brace is a significant factor affecting the imbalance coefficient of tension–compression bearing capacity, with longer braces resulting in a larger imbalance coefficient. The 3 m BRB shows less deviation from the mean values of various fatigue parameters, indicating more stable low-cycle fatigue performance. Within the same structure, shorter BRBs with larger design displacements achieve higher energy dissipation efficiency, allowing for more effective utilization of their energy dissipation capacity. This study’s conclusions provide valuable references for designers in the rational selection of BRBs of different lengths in actual engineering projects and offer preliminary insights into the energy dissipation efficiency of BRBs of varying lengths within a structure.